History, providence, and eschatology - Stievermann, Jan (The Oxford handbook of Jonathan Edwards, 2021)
This chapter discusses Edwards’s view of history and the end times. It does so by examining four interlocking frameworks of interpretation that Edwards inherited from Reformed-Puritan theology: first, a general approach to relating the Bible and history; second, an intense kind of providentialism; third, specific forms of biblical theology aiming toward an integrated salvation history; and fourth, a futurist type of millennialist eschatology. What emerges from this is the picture of an Edwards who was, for the most part, a traditionalist. At the same time, he, like many of his peers, engaged with the intellectual discourses of the Enlightenment, both by partaking in them and criticizing their perceived excesses. Edwards’s version of a moderate Protestant Enlightenment produced a deepened, eschatologically inflected interest in redemption history, which he understood as a progressive continuum. Within this framework of history Edwards came to assign crucial significance to revivals.